In situ Molecular Hybridization of Kaposi, s Sarcoma Associated Virus (Human Herpes Virus 8) in Nasopharyngeal Carcinoma Tissues - Zainab A. Hamid1 , Zahraa Ali Abdullah2 , Isra’a Mahdi Al-Sudani3 , Saad Hasan Mohammed Ali4 , Shaki (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Viral, dietary and genetic factors are implicated in the etiology ofnasopharyngeal cancer, a raretype of head and neck cancers. Unlike other viruses, HHV-8 encodes several human cytokines homologuesand regulatory genes that play important roles in the viral pathogenesis.Objective: To analyze the rates of HHV-8 infection in tissues obtained from a group of patients withnasopharyngeal carcinoma and inflammatory nasal polyps (INP) .Patients and Method: One hundred- thirty formalin-fixed, paraffin- embedded nasopharyngeal carcinomaand nasal inflammatory polyps tissues enrolled in this study; 65 nasopharyngeal tissue biopsies fromnasopharyngeal carcinoma; 35 tissue biopsies from nasal inflammatory polyps and 30 nasopharyngealtissues with unremarkable pathological changes, as apparently healthy tissuecontrol. Detection of HHV-8was done by chromogenic in situ hybridization (CISH) technique detection system.Results: In nasopharyngeal carcinoma tissues, the HHV-8- DNA positive CISH reactions were detected in23.1% while in nasal inflammatory polyps tissues HHV-8-positive CISH reactions were found in 8.6% ofthe examined tissues. The correlation between HHV-8 and NPC & INP was highly significant (P= 0.001).Conclusion: Significant HHV-8 detection in nasopharyngeal carcinoma & inflammatory nasal polypstissuescould point for their possible role in either pathogenesis or carcinogenesis of both these lesions.